М
Молодежь
К
Компьютеры-и-электроника
Д
Дом-и-сад
С
Стиль-и-уход-за-собой
П
Праздники-и-традиции
Т
Транспорт
П
Путешествия
С
Семейная-жизнь
Ф
Философия-и-религия
Б
Без категории
М
Мир-работы
Х
Хобби-и-рукоделие
И
Искусство-и-развлечения
В
Взаимоотношения
З
Здоровье
К
Кулинария-и-гостеприимство
Ф
Финансы-и-бизнес
П
Питомцы-и-животные
О
Образование
О
Образование-и-коммуникации
Polinka1353
Polinka1353
05.10.2022 17:27 •  Алгебра

Найти значение выражения 0,4x-10 при x =-15

👇
Ответ:
Kats203
Kats203
05.10.2022

просто подставить:

0.4(-15)-10=-6-10=-16

4,8(52 оценок)
Открыть все ответы
Ответ:
Лизатян4
Лизатян4
05.10.2022

Объяснение:

505. 3√a -2√a=(3-2)√a=√a

√с +10√с -14√с=(1+10-14)√c=-3√с

9√6 -2√3 +8√3 -3√6=(9-3)√6-(2-8)√3=6√6 +6√3=6(√(3·2) +√3)=6√3 ·(√2 +1)

507. 2√(4x) +6√(16x) -√(625x)=2·2√x +6·4√x -25√x=(4+24-25)√x=3√x

3√(0,09y) -0,6√(144y) +18/11 √(121/36 ·y)=3√(9/100 ·y) -0,6·12√y +18/11 ·11/6 √y=3·3/10 √y -7,2√y +3√y=(0,9-7,2+3)√y=-3,3√y=-(33√y)/10

510. 4√700 -27√7=4√(7·100) -27√7=4·10√7 -27√7=(40-27)√7=13√7

√75 -6√3=√(25·3) -6√3=5√3 -6√3=(5-6)√3=-√3

2√50 -8√2=2√(25·2) -8√2=2·5√2 -8√2=(10-8)√2=2√2

5√12 -7√3=5√(4·3) -7√3=5·2√3 -7√3=(10-7)√3=3√3

3√72 -4√2 +2√98=3√(36·2) -4√2 +2√(49·2)=3·6√2 -4√2 +2·7√2=(18-4+14)√2=28√2

1/3 √108 +√363 -2/9 √243=1/3 √(36·3) +√(121·3) -2/9 √(81·3)=1/3 ·6√3 +11√3 -2/9 ·9√3=(2+11-2)√3=11√3

4,5(68 оценок)
Ответ:
Jannalizahappy
Jannalizahappy
05.10.2022

1)       ac2-ad+c3-cd-bc2+bd=  = (ac2 – ad) + (c3 –

bc2) + (bd – cd) = a·(c2 – d) + c2·(c – b) + d·(b     – c) = a·(c2 – d) +

c2·(c – b) – d·(c – b) = a·(c2 – d) + c2·(c – b) – d·(c – b) = a·(c2 –

d) + (c – b)·(c2 – d) = (c2 – d)·(a + c – b)

2)  mx2+my2-nx2-ny2+n-m= x2 ( m - n ) + y2 ( m - n ) - ( m - n ) = ( m-n ) (x2 + y2 - 1 )  

3)   am2+cm2-an+an2-cn+cn2= m2 (a + c ) + n2 ( a + c ) - n ( a + c ) = ( a+ c) ( m2 + n2 - n) 

4)   xy2-ny2-mx+mn+m2x-m2n= y2 ( x - n ) + m2 ( x - n) - m ( x - n ) = ( x-n) ( y2 + m2 - m ) 

5)   a2b+a+ab2+b+2ab+2=ab ( a + b + 2 )   + ( a+ b+ 2 ) = 2 ( a+ b + 2 ) 

6)   x2-xy+x-xy2+y3-y2=   x ( x –   y + 1) –   y 2 ( x –   y + 1)=( x –   y + 1)( x –   y 2 ).

4,4(4 оценок)
Это интересно:
logo
Вход Регистрация
Что ты хочешь узнать?
Спроси Mozg
Открыть лучший ответ